Planteamiento didáctico del proceso lector. - Quintanal Díaz, J. (Didáctica. Lengua y Literatura, 1996)
`¡`bis article presents a methodological outline to complete children’s reading comprehension learning. Aceording to the autor, te development of reading has two aspects: one intectretative and another motivating. Besides, each of them has three levels where there should he a didactie interventión in order to get true readers.